Clinical efficacy and safety of radiofrequency catheter ablation for atrial fibrillation in patients aged ≥80 years. Issue 8 (20th July 2020) - Zhou, Genqing; Cai, Lidong; Wu, Xiaoyu; Zhang, Liangfeng; Chen, Songwen; Lu, Xiaofeng; Xu, Juan; Ding, Yu; Peng, Shi; Wei, Yong; Liu, Shaowen
Abstract: Aim: To evaluate the clinical safety and efficacy of radiofrequency catheter ablation for atrial fibrillation (AF) in patients aged ≥80 years. Methods: A total of 333 AF patients aged ≥60 years were enrolled, who underwent contact force‐guided radiofrequency catheter ablation with uninterrupted anticoagulation. All patients were followed‐up for at least 12 months. Success was defined by the absence of episodes of AF/atrial tachycardia lasting more than 30 seconds after a 3‐month blanking period, without antiarrhythmic drugs. Results: Compared to patients aged 60‐79 years (Group 2, n = 244), patients aged ≥80 years (Group 1, n = 89) were presented with higher rate of diabetes (36.0% vs 22.1%, P  = .011), lower body mass index (23.4 ± 3.1 vs 24.9 ± 3.4 kg/m 2, P  = .001), lower creatinine clearance (56.9 ± 16.5 vs 83.3 ± 24.5 mL/min, P  < .001), higher CHA2 DS2 ‐VASc score (4.3 ± 1.3 vs 3.3 ± 1.4, P  < .001), and HAS‐BLED score (2.2 ± 0.8 vs 1.8 ± 0.8, P  < .001). Wide antral pulmonary vein isolation was achieved in all patients, and there was no significant difference in procedure time, ablation time, fluoroscopy time, and complications rate between two age groups ( P  > .05). After a mean follow‐up of 24.4 ± 9.6 months, the overall success rate was 78.2% in Group 1 and 78.9% in Group 2 ( P  = .622). Conclusions: Radiofrequency ablation with contact force sensing catheters for AF is safe and effective in selected patients aged ≥80 years.